2001
DOI: 10.1046/j.1440-1584.2001.00366.x
|View full text |Cite
|
Sign up to set email alerts
|

Serving Rural Australia With Reproductive Health Expertise

Abstract: This study aimed to review the use of reproductive health services in Family Planning clinics by women from rural (non-metropolitan) Australia through a retrospective analysis of data collected at clinics of seven state/territory Family Planning Organisations (FPO). From a total of 146 157 client visits to FPO clinics between July 1998 and June 1999, 42 497 (29.1%) were by clients who lived outside metropolitan areas. Some 97% of clients were women. Our results show the use of reproductive health services by w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…It has previously been recognised that rural-located women are more likely to use LARC compared with city-living women both in Australia and the USA 23 24. A number of explanations have been postulated for this difference including access and travel distances, differing patient needs and differing GP skill sets 23 25. Our finding that LARC prescribing is associated with women managed in practices in lower SEIFA index areas reflects previous findings that LARC is used more frequently by women who do not have a university qualification, and those working in manual, trade or service occupations 23.…”
Section: Discussionsupporting
confidence: 77%
“…It has previously been recognised that rural-located women are more likely to use LARC compared with city-living women both in Australia and the USA 23 24. A number of explanations have been postulated for this difference including access and travel distances, differing patient needs and differing GP skill sets 23 25. Our finding that LARC prescribing is associated with women managed in practices in lower SEIFA index areas reflects previous findings that LARC is used more frequently by women who do not have a university qualification, and those working in manual, trade or service occupations 23.…”
Section: Discussionsupporting
confidence: 77%
“…It is difficult to interpret these findings because of the subjective nature of the measure used. Further examination of more objective measures of access to health services (such as distance between the woman's home and the nearest service) in protecting against STI among Australian women may be warranted particularly in relation to planning services for rural areas (Mirza, Kovacs, & Kinfu, 2001;Mirza, Kovacs, & McDonald, 1998). This study showed that despite adjusting for a range of factors, including area of residence, perceived quality of access to Women's Health or Family Planning Centres was protective for later STI diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In regards to family planning services in Australia, retrospective data analyses of the seven state/territory family planning organisations (excluding South Australia) found that between July 1998 and June 1999, 29.1% of the 146,157 clients were from rural areas (Mirza, Kovacs, & Kinfu, 2001 repercussions. These include less chance of further education, having a career, and finding subsequent employment, which may in turn result in greater chance of long term socioeconomic disadvantage.…”
Section: Family Planning In Rural Communitiesmentioning
confidence: 99%